2020
DOI: 10.3389/feart.2020.539377
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Scientific Approaches to the Study of Terroir Are Needed!

Abstract: Terroir is a French term with roots in the Latin term terra meaning ground or land. In the international wine jargon, the term has assumed a more specific and nuanced meaning: it is the result of "collective knowledge of the interactions" between the environment and the vines mediated through human action and "providing distinctive characteristics" to the final product (i.e., wine; OIV, 2010). Terroir is not just a geographical site, but includes: (i) the physical environment (e.g., climate, geology, soil, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Sadly, this is a process that in some regions has arguably become captive to wine writers and marketeers with many of the 'stories' characterised by a lack of underpinning science and/or focused on variation in a single attribute (Bramley, 2017). A similar comment could be made in relation to much of the popular commentary on terroir more broadly (Brillante et al, 2020).…”
Section: Case Study 2 Sub-regionalisation In the Barossa Valleymentioning
confidence: 81%
See 2 more Smart Citations
“…Sadly, this is a process that in some regions has arguably become captive to wine writers and marketeers with many of the 'stories' characterised by a lack of underpinning science and/or focused on variation in a single attribute (Bramley, 2017). A similar comment could be made in relation to much of the popular commentary on terroir more broadly (Brillante et al, 2020).…”
Section: Case Study 2 Sub-regionalisation In the Barossa Valleymentioning
confidence: 81%
“…Conversely, if terroir is expressed quite differently by different varieties, then the problem becomes much more complex than it already appears. In both Marlborough and the Barossa, the effects of climate change will doubtless also need to be considered (Petrie and Sadras, 2008;Brillante et al, 2020;Salinger et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For obvious reasons, it might therefore be suggested that establishment of territorial branding may be especially difficult for New World wine countries, equally so for regions within them, and extremely difficult for subregions within these. Attempts at improved understanding of terroir might therefore be better directed at improved management of grape and wine production (Bramley 2017, Brillante et al 2020) than at marketing objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Much previous research into these factors, especially in the context of terroir zoning, has relied on a mix of heuristics, rules of thumb and qualitative expert opinion of the merits of the wines produced in particular regions. Brillante et al (2020) have recently argued, however, that terroir research should be based on unbiased approaches. Thus, rather than focussing on conformity to previously defined terroir units (e.g.…”
Section: Introductionmentioning
confidence: 99%